CALLIGRAPHY IN DIGITAL ARCHITECTURE: UNDERSTANDING THE AESTHETIC FUSION IN DESIGN STUDIO - Quratulain Asghar; Dr. Mamuna Iqbal; Dr Munazzah Akhtar (International Journal of Contemporary Issues in Social Sciences, 2024)
This research explores an innovative approach integrating calligraphy, architecture, and digital tools within an architectural studio. It examines the design process and learning outcomes of two studio projects that combine traditional calligraphic techniques with contemporary digital architecture. The exploration aims to address the increasing homogenization of architectural designs in the digital age by offering a unique solution that integrates art, architecture, and technology. The study was conducted over four months during the fall semester of 2023 at the 4th-year level in the Architecture Department at the University of Engineering and Technology Lahore. The research recognizes the pressing need to develop a framework that allows students to leverage digital tools in their architectural workflows while preserving traditional practices’ expressive and crafted qualities. Students motivated by a shared passion for calligraphy and architecture undertook this research to bridge the gap between traditional craftsmanship and cutting-edge design. This studio practice presents a transformative approach to architectural design and expression, where students employ calligraphic tools to create hand-drawn architectural elements that emphasize the expressive nature of letterforms and strokes.